Walmart in China - Chan, Anita (ILR Press, 2011)
Walmart and "Made in China" are practically synonymous; Walmart imports some 70 percent of its merchandise from China. Walmart is now also rapidly becoming a major retail presence there, with close to two hundred Walmarts in more than a hundred Chinese cities. What happens when the world's biggest retailer and the world's biggest country do business with each other? In this book, a group of thirteen experts from several disciplines examine the symbiotic but strained relationship between these giants. The book shows how Walmart began cutting costs by bypassing its American suppliers and sourcing directly from Asia and how Walmart's sheer size has trumped all other multinationals in squeezing procurement prices and, as a by-product, driving down Chinese workers' wages.China is also an inviting frontier for Walmart's global superstore expansion. As China's middle class grows, the chain's Western image and affordable goods have become popular. Walmart's Arkansas headquarters exports to the Chinese stores a unique corporate culture and management ideology, which oddly enough are reminiscent of Mao-era Chinese techniques for promoting loyalty. Three chapters separately detail the lives of a Walmart store manager, a lower-level store supervisor, and a cashier. Another chapter focuses on employees' wages, "voluntary" overtime, and the stores' strict labor discipline. In 2006, the official Chinese trade union targeted Walmart, which is antilabor in its home country, and succeeded in setting up union branches in all the stores. Walmart in China reveals the surprising outcome.Contributors: Diana Beaumont, coeditor of China Labor News Translations; Anita Chan, University of Technology, Sydney; David J. Davies, Hamline University; Nelson Lichtenstein, University of California, Santa Barbara; Scott E. Myers, Monterey Institute of International Studies; Eileen Otis, University of Oregon; Pun Ngai, Hong Kong Polytechnic University; Katie Quan, University of California, Berkeley; Taylor Seeman, Hamline University; Kaxton Siu, Australian National University; Jonathan Unger, Australian National University; Xue Hong, East China Normal University; Yu Xiaomin, Beijing Normal University.